Interleukin 4/13 Receptors: An Overview of Genes, Expression and Functional Role in Teleost Fish - Imarai-Bahamonde, C; Maisey-Munoz, K (Elsevier Ltd, 2017)
In superior vertebrates, Interleukin 4 (IL-4) and Interleukin 13 (IL-13) play key and diverse roles to support immune responses acting on cell surface receptors. When stimulated, receptors activate intracellular signalling cascades switching cell phenotypes according to stimuli. In teleost fish, Interleukin 4/13 (IL-4/13) is the ancestral family cytokine related to both IL-4 and IL-13. Every private and common receptor subunit for IL-4/13 have in fish at least two paralogues and, as in mammals, soluble forms are also part of the receptor system. Reports for findings of fish IL-4/13 receptors have covered comparative analysis, transcriptomic profiles and to a lesser extent, functional analysis regarding ligand-receptor interactions and their biological effects. This review addresses available information from fish IL-4/13 receptors and discusses overall implications on teleost immunity, summarized gene induction strategies and pathogen-induced gene modulation, which may be useful tools to enhance immune response. Additionally, we present novel coding sequences for Atlantic salmon (Salmo salar) common gamma chain receptor (γC), Interleukin 13 receptor alpha 1A chain (IL-13Rα1A) and Interleukin 13 receptor alpha 1B chain (IL-13Rα1B). © 2017 Elsevier Ltd